Heterogeneity of the resistance to gefitinib treatment in a non‐small cell lung cancer patient with active epidermal growth factor receptor mutation. Issue 1 (1st November 2016) - Xu, Chong‐Rui; Zhong, Wen‐Zhao; Zhou, Qing; Zhang, Xu‐Chao; Yang, Jin‐Ji; Wu, Yi‐Long
Abstract : We report the case of a 37‐year‐old male non‐small cell lung cancer patient with an active epidermal growth factor receptor (EGFR) mutation who received gefitinib as first‐line treatment. After 13.7 months, the patient experienced disease progression and was treated with platinum‐based doublet chemotherapy plus gefitinib for 5.4 months. A subsequent lung biopsy showed cMET overexpression; therefore, the patient received a cMET inhibitor with the gefitinib. The response in the different lesions of several organs was diverse. Stable disease was achieved in the lung lesion; however, the liver metastases enlarged. A liver biopsy found T790M mutation in EGFR exon 20, thus, third generation EGFR‐tyrosine kinase inhibitors were used and a partial response was achieved.